Secondary Victimisation and Retributive Justice Erosion amid Declining Trust in Police - Dian Rusmana; Ine Fauzia (Journal of Dual Legal Systems, 2026)
This article examines the phenomenon of "noodweer" (self-defence) in cases of violent theft, which is triggered by public distrust of police performance, through a criminological lens. Focussing on cases of motorcycle theft disguised as illegal debt collection and the public's response, which sometimes leads to vigilantism in various regions, this research analyses nood weer as a criminological response to structural tensions and the failure of social control caused by institutional dysfunction. This study deeply highlights how the police's failure to provide protection and a sense of security creates secondary victimisation for perpetrators who are forced to act outside the law. Analysis shows that the significant decline in public trust in the police significantly erodes the principle of retributive justice, as public perception of punishment fairness becomes blurred when institutional failure factors are not considered. A comparison of responses across different regions based on news reports indicates that public distrust and the effectiveness of law enforcement are key determining factors in the emergence of this phenomenon. The social and ethical implications of this phenomenon underscore a crisis of legitimacy for law enforcement institutions, demanding the strengthening of police professionalism, accountability, and transparency, as well as a review of debt collection regulations and the strengthening of alternative dispute resolution systems to sustainably rebuild public trust.